Calcium oxalate precipitation by diffusion using laminar microfluidics: toward a biomimetic model of pathological microcalcifications. Issue 7 (14th March 2016) - Laffite, G.; Leroy, C.; Bonhomme, C.; Bonhomme-Coury, L.; Letavernier, E.; Daudon, M.; Frochot, V.; Haymann, J. P.; Rouzière, S.; Lucas, I. T.; Bazin, D.; Babonneau, F.; et al.
Abstract : The effect of mixing calcium and oxalate precursors by diffusion at miscible liquid interfaces on CaOx crystalline phases is studied using a microfluidic channel. Abstract : The effect of mixing calcium and oxalate precursors by diffusion at miscible liquid interfaces on calcium oxalate crystalline phases, and in physiological conditions (concentrations and flow rates), is studied using a microfluidic channel. This channel has similar dimensions as the collection duct in human kidneys and serves as a biomimetic model in order to understand the formation of pathological microcalcifications.